Clinical and sociodemographic correlates of neonatal jaundice at a tertiary health facility in Lagos, Nigeria - Oyejoke Oyapero; Aruma E Disu; Fidelis O Njokanma (Advances in Human Biology, 2018)
Background: Varied aetiologies have been proposed for the prevalence of neonatal jaundice (NNJ) in different parts of Nigeria. The aim of this study was to determine the clinical and sociodemographic correlates of NNJ in a cohort of neonates presenting at a Tertiary health Facility in Lagos, Nigeria. Materials and Methods: One hundred and fifty consecutive neonates that presented at the neonatal unit of the hospital were enlisted for the study after checking them with set inclusion and exclusion criteria. The transcutaneous bilirubin (TcB) readings of the individuals were obtained on the forehead, sternum and abdomen of the calm neonate in a supine position and blood samples for total serum bilirubin estimation were drawn from a peripheral vein within 10 min of TcB measurement. Results: One hundred and fifty neonates were included in the study of which 89 (59.33%) were males and 61 (40.67%) were females. Mothers that had only a primary level of education had babies that presented with significantly higher bilirubin values (P = 0.000). Male neonates, those that presented after 48 h, those between 40 and 42 weeks' gestational age and those that were <2.5 kg birth weight also had higher values though it was not statistically significant. Those that were delivered at home or in a church, delivered by an auxiliary nurse or a traditional birth attendant and those with jaundice extending to the sole of the feet also presented with significantly higher mean bilirubin scores (P = 0.000). Conclusion: Majority of individuals in this study with NNJ were males, while those delivered at home or in a church or by traditional birth attendants and auxiliary nurses and had mothers that were poorly educated had higher mean bilirubin values. It is thus imperative that advocacy is increased to intervene on modifiable risk factors for this condition.